Perlindungan Hukum terhadap Kekerasan Seksual pada Perempuan: Sebuah Studi Peraturan Perundang-Undangan - Salwa Salsabilla; Imran Bukhari Razif; Ulil Albab (SIGn Jurnal Hukum, 2023)
This study aims to examine the legal protection framework against sexual violence towards women based on Law Number 12 of 2022. This study uses normative legal research methods with a statute approach. These legal materials were collected through a systematic literature review. The results show that Law Number 12 of 2022 has introduced a new paradigm in enhancing legal protection for women victims of sexual violence. Law Number 12 of 2022 provides guarantees of protection and the fulfillment of rights for victims. It also emphasizes the proactive role of the state in assuring and implementing these rights. In providing safety-assuring assistance, the central and regional governments have a strategic role in administrating integrated services encompassing treatment, protection, and recovery for sexual violence victims. Therefore, it is recommended for stakeholders, especially the central and regional governments, to increase the intensity and quality of integrated services that encompass the treatment, protection, and recovery of victims of sexual violence, primarily women. Moreover, the relevant agencies must ensure that every victim has full access to the information and support required by the rights guaranteed by Law Number 12 of 2022. A close collaboration between the government, civil society organizations, and the community can reinforce the implementation of Law Number 12 of 2022. Lastly, educating the general public about protecting women from sexual violence should be continuously enhanced to foster an environment free from violence.